تحسين أداء متحكم ضبابي لملاحقة مسار نقطة الاستطاعة الأعظمية في الخلايا الشمسية باستخدام الخوارزمية الجينية - قزي, صالح; خنوفه, محمد العيد (Université d'El Oued, 2021)
"For importance of exploiting the alternative resources in generating electrical energy ,this research shows the study, analysis and simulation of photovoltaic system to maximum power point tracking of path in solar cells system that composed of: PV panel, fuzzy controller, DC-DC converter (buck converter) and load. A tracking technique that depend on fuzzy logic controller is used for maximum power point tracking (MPPT) for getting the maximum power from PV panels.Two types of fuzzy controllers are used: Mamdani and Sugeno High stability is achieved at high values of a fixed period of Duty Cycle by using DCDC converters of the type buck converter. A genetic algorithm used to improve the performance of the most suitable controller to achieve more stability, less error and less stability time. This thesis shows effectiveness and quality of the performance Mamdani type-fuzzy logic controller in maximum power point tracking of path and the genetic algorithm added a good improving of them wise speed of stability , reduce error ,absence overshot and very high stability on the peak. Photovoltaic control system is modeled and simulated for maximum power point path tracking by using MATLAB/Simulink environment." "نظرا لأهمية استغلال مصادر الطاقات البديلة ومنها الطاقة الشمسية في توليد الطاقة الكهربائية يقدم هذا البحث دراسة وتحليل ومحاكاة نظام كهروضوئي لملاحقة مسار نقطة الاستطاعة الأعظمية في نظام الخلايا الشمسية المكون من : الألواح الكهروضوئية والمتحكم الضبابي والُمبّدل المستمر الخافض للجهد والحمل. بسبب أهمية ملاحقة نقطة الاستطاعة العظمى(MPPT ) للحصول على الاستطاعة العظمى من الألواح الكهروضوئية, تم اختيار تقنية ملاحقة تعتمد على المتحكم الضبابي. تم استخدام كل من المتحكمين الضبابيين من نوع Mamdani ونوع Sugeno . تحقق استقرار عال عند القيم العالية لدورة التشغيل (Duty Cycle) باستخدام مبّدلات التيار المستمر من النوع الخافض للجهد (Buck Converter). تم تطبيق الخوارزمية الجينية من أجل تحسين أداء المتحكم الضبابي تحقيق المزيد من الاستقرار وتقليل الخطأ وزمن الاستقرار. بينت الدراسة فعالية وجودة أداء المتحكم الضبابي Mamdani في ملاحقة مسار نقطة الاستطاعة الأعظمية وأضافت تحسين ا الخوارزمية الجينية جيدا على أدائه من ناحية سرعة الاستقرار وتقليل الخطأ وانعدام التجاوز. تمت محاكاة مكونات النظام الكهروضوئي لملاحقة مسار نقطة الاستطاعة الاعظمية باستخدام بيئة MATLAB/Simulink . "
RESEAUX ELECTRIQUESمذكرة ماستر تخصص
Keywords: "photovoltaic System, Maximum Power Point Tracking (MPPT),Fuzzy Logic Controller, Buck Converter, Pulse Wide Modulation(PWM),Genetic Algorithm."; "النظام الكهروضوئي , ملاحقة نقطة الاستطاعة الأعظمية(MPPT) , المتحكم الضبابي, المبدل المستمر الخافض للجهد , معدل عرض نبضات PWM , الخوارزمية الجينيةGA."